The perceptions and management of psychosis amongst Traditional Healers living in the township of Umlazi KwaZulu-Natal - Maqalika, Rethabile (My University, 2020)
The conceptualization of mental illness varies across cultures and research has shown that the perceptions of mental illness are heavily influenced by spiritual and cultural beliefs. Some overlaps exist between psychosis and some cultural phenomena within the South African context and Traditional Healers have been found to play a major role in the management of mental illness. Therefore, the aim of this study was to explore the perceptions and management of psychosis by Traditional Healers of Umlazi KwaZulu-Natal. A qualitative research study was conducted where nine Traditional Healers from Umlazi Township participated in semi-structured interviews in order to ascertain their perceptions and management of psychosis. Thematic analysis was utilised to analyse the data findings and themes centred on the perceptions of psychosis by Traditional Healers, aetiology of mental illness, diagnosing mental illness, perceptions of mental illness as well as treatment of mental illness emerged. The results of the research study suggest that some gaps still exist in the perceptions and understandings of psychosis between the western mental health practitioners and indigenous healers. Collaboration between these two entities is essential in the understanding and management of psychosis from the western and indigenous perspective
A research project submitted in the partial fulfilment of the requirements for the degree of MA by Coursework and Research Report in the field of Clinical Psychology in the Faculty of Humanities, University of the Witwatersrand, Johannesburg, 2020
Keywords: Healers--South Africa; Herbalists--South Africa; Ancestor worship--South Africa